The effect of pregnancy intention on maternal prenatal behaviours and parent and child health: results of an Irish cohort study - MC CRORY, CATHAL (My University, 2013)
Background: Unintended pregnancy is associated with increased risk for adverse neonatal and early childhood outcomes spanning an array of indicators, but it remains unclear whether these risks hold independent of other biological, social and environmental risk factors. Methods: This study uses data from the first wave of the ‘Growing Up in Ireland Study’, a large nationally representative cohort study of more than 11 000 infants, to examine the risk factors associated with unintended pregnancy. Adopting a staged approach to the analysis, the study investigates whether pregnancy intention influences maternal health behaviours during pregnancy independent of background characteristics, and whether pregnancy intention carries any additional risk for adverse infant and maternal health outcomes when we adjust for background characteristics and prenatal behaviours. Results: The study confirmed that sociodemographic factors are strongly associated with unintended pregnancy and that unintended pregnancy is associated with a range of health compromising behaviours that are known to be harmful to the developing fetus. While there was little evidence to suggest that pregnancy intention was associated with adverse neonatal outcomes or developmental delay independent of other covariates, there was strong evidence that intention status had a bearing on the mother's psychosocial health. Unintended pregnancy was associated with increased risk of depression (risk ratio 1.36 [95% confidence interval 1.19, 1.54]), and higher parenting stress (risk ratio 1.27 [95% confidence interval 1.16, 1.38]). Conclusions: Ascertaining the mother's pregnancy intention during the first antenatal visit may represent a means for monitoring those at greatest risk for adverse mother and child outcomes.
PUBLISHED
Keywords: Pregnancy intention; Neonatal health; Child development; Parental psychosocial health; Ageing